Perspectives économiques et financières trimestrielles - Landry, Jean-Luc (Assurances, 1983)
ln his excellent study of the economic and financial situation in the United States and Canada, Mr. Jean-Luc Landry reviews the conditions prevailing in recent months. During this period, a number of noteworthy events have occurred and the firm Bolton Tremblay Inc. through one of its economists, has provided comments on each. We are most grateful to Bolton Tremblay Inc. for permitting us to open our July issue with their study for it sheds a well-defined light on the economic situation.